Climatology of UTLS Ozone and the ratio of ozone and potential vorticity over northern Europe - Rao, T. N.; Kirkwood, S.; Arvelius, J.; Kivi, R.; von der Gathen, Peter (Journal of Geophysical Research: Atmospheres, 2003)
Annual and interannual variations of ozone in the upper troposphere and lower stratosphere (UTLS) region have been studied using ozonesonde data collected between 1994 and 2001 at several northern European stations. The climatology of ozone exhibits a prominent annual cycle in the UTLS region. The observed change in the phase of the annual cycle from late spring-early summer at 500 hPa to spring at 200 hPa and to winter-early spring at 100 hPa shows the switching of the ozone control from photochemical to dynamical. Traces of interannual variation in the lower stratosphere are seen not only in the upper troposphere but also in the middle troposphere (not necessarily always) indicating the dynamical influence on tropospheric ozone budget. Further, the correlation between ozone mixing ratio and potential vorticity (PV) is studied at three northern high-latitude stations. As expected, a good correlation is found in the lower stratosphere, while the correlation is fair in the middle troposphere, except during summer over the European Arctic. This weak correlation at high latitudes indicates the dominance of photochemistry over dynamics in the presence of prolonged hours of solar illumination. The correlation coefficients derived at high latitudes are smaller than those reported at midlatitudes. This could be due to the greater number of tropopause folds at midlatitudes than at high latitudes and this eventually leads to the conclusion that the downward cross-tropopause flux is greater at midlatitudes than at high latitudes. Absence of a significant north-south gradient in the ozone/PV ratio in the lower stratosphere suggests that a single ozone/PV ratio (however, the ratio varies with month) can be used to convert global PV fluxes to ozone fluxes. A few cases of tropopause folds (only one case study is reported in the present study) are selected and studied in detail with the help of a very high frequency radar and meteorological analysis. The ratio between ozone and PV for these case studies agrees reasonably well ...